Теоретичне моделювання межі поділу кремнезем – водний розчин електроліту - Kravchenko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
Quantum chemical calculations on the equilibrium spatial structure and formation energy of hydrated complexes of electrolytes (salt of sodium chloride, inorganic acids, inorganic and organic bases) molecules on the surfaces of silica particles have been carried out within the frameworks of ab initio Hartree-Fock and density functional theory methods. The hydration mechanism has been examined of electrolytes molecules and the most probable routes have been shown of adsorption of associative hydrated complexes on high disperse silica surface.